DEVELOPMENT OF DIGITAL LITERACY-BASED DESCRIPTIVE TEXT TEACHING MATERIALS FOR ISLAMIC JUNIOR HIGH SCHOOL (MTS) STUDENTS - Panjaitan, Devi; Faridah, Faridah (Universitas Muhammadiyah Makassar, 2025)
Descriptive writing skills are an essential component of Indonesian language learning. However, many students struggle to express their ideas coherently and clearly. One contributing factor is the lack of contextual and engaging teaching materials. This study aims to develop digital literacy-based teaching materials for descriptive texts to improve the writing skills of seventh-grade students at MTs Zia Salsabila Bandar Setia. The research employed a Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques included expert validation (content, language, and media), questionnaires for students and teachers, and writing tests (pretest and posttest). Data were analyzed using descriptive quantitative methods by calculating percentages and N-gain scores. The validation results indicated that the teaching materials were highly appropriate, with scores of 100% from the content expert, 93% from the language expert, and 90% from the media expert. Practicality was rated as excellent, based on student responses from the small group (91.8%) and large group (94.56%), and teacher responses (96%). The effectiveness of the materials was demonstrated by an increase in the average score from the pretest (56%) to the posttest (89%), with an N-gain score of 0.75, indicating a high level of improvement. These findings show that the digital literacy-based descriptive text teaching materials are effective in enhancing students’ writing skills. The study recommends the use of such materials as an innovative and interactive alternative in Indonesian language instruction.